2019
DOI: 10.1186/s40635-019-0251-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the source and prognostic utility of cfDNA in trauma and sepsis

Abstract: Background Circulating cell-free DNA (cfDNA) may contribute to the pathophysiology of post-injury inflammation and coagulation in trauma. However, the source and mechanism of release of cfDNA in trauma is not well understood. One potential source of cfDNA is from Neutrophil Extracellular Traps (NETs), released by activated neutrophils during the process of NETosis. The primary objective of our study was to determine if cfDNA has prognostic utility in trauma. The secondary objective of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 35 publications
1
51
0
1
Order By: Relevance
“…Regarding the total amount of cfDNA, we observed that this value differs depending on the clinical or disease phenotype and genotype of patients. cfDNA is a variable parameter, that even in healthy individuals presents significant variations due to inflammation, injury or exercise 20–22 . However, irrespective of disease phenotype our MPN samples showed a significantly higher amount of cfDNA than those of healthy controls, indicating a higher release of cfDNA in plasma from MPN clonal cells.…”
Section: Discussionmentioning
confidence: 75%
“…Regarding the total amount of cfDNA, we observed that this value differs depending on the clinical or disease phenotype and genotype of patients. cfDNA is a variable parameter, that even in healthy individuals presents significant variations due to inflammation, injury or exercise 20–22 . However, irrespective of disease phenotype our MPN samples showed a significantly higher amount of cfDNA than those of healthy controls, indicating a higher release of cfDNA in plasma from MPN clonal cells.…”
Section: Discussionmentioning
confidence: 75%
“…Pan et al found that the level circulating H3Cit was significantly higher at 0.5, 3, 12, and 24 hours after LPS injection in LPS-treated mouse group than that in control group, revealing its potential ability as a sensitive and longlasting biomarker (86). Another observational study also showed an elevated H3Cit level of septic patients, which is far more that of trauma patients (87). The same article confirmed the utility of histones in determining disease progression of sepsis and suggested that H3Cit might serve as an indicator for antibiotics treatment (87).…”
Section: Circulating Histones In Sepsis As Potential Diagnostic or Prmentioning
confidence: 97%
“…Hypercitrullination weakens the histone interaction with DNA, thus unfolding the tightly packed chromatin 10 (Figure 1B) and contributing to NET formation (Figure 1C). H3Cit is therefore considered a useful marker of NET formation 23‐34 …”
Section: Introductionmentioning
confidence: 99%